Effects of hydration on elite surfing performance - Ali, A.; Foskett, A.; Carrasco, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Sports performed in hot ambient conditions with minimal reliance on fluid ingestion are likely to be affected by the physical, cognitive and skill performance decrements attributed to exercise-induced dehydration. PURPOSE: To determine whether surfing performance is affected by dehydration and whether fluid ingestion can attenuate any performance decrements. METHODS: Twelve male national (Australia) and international level surfers completed two 100-min surfing sessions, in wetsuits, separated by seven days. Following a randomised cross-over design, one trial required the consumption of 3 ml•kg-1 body mass (BM) of water at 20 min intervals (FL) whilst in the other trial no fluid was consumed (NF). A battery of cognitive tests, upper and lower-body muscular endurance tests and hydration status were assessed prior to and immediately following the surfing session. Performance was assessed, in accordance with the Association of Surfing Professionals (ASP) World Tour guidelines, for two 20 min periods during each trial. Ambient conditions and wave quality were consistent with those expected at Sydney`s northern beaches and were similar between trials. RESULTS: BM loss was greater in NF than in FL (3.9 ± 0.7% vs. 1.6 ± 0.7%; P<0.05). Surfing performance was significantly impaired in NF with lower scores (20.3 ± 7.1%) in this trial. Cognitive function, upper- and lower body muscular endurance were impaired in NF (P<0.05) whereas only upper-body muscular endurance decreased following FL (P<0.05). CONCLUSIONS: Body mass losses during surfing are severe enough to significantly impair surfing performance, cognitive function and muscular endurance. Consumption of 3 ml•kg-1 BM water every 20 min may attenuate these decreases in performance.